The Impact of AYIMUN Participation on Indonesian EFL University Students’ Public Speaking Confidence: A Qualitative Case Study - Andi Rahmayanti; Syarifuddin Dollah (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2026)
Public speaking confidence constitutes a fundamental communicative competence for university students operating in increasingly globalized academic and professional environments. This qualitative case study investigates the impact of participation in the Asia Youth International Model United Nations (AYIMUN) on the public speaking confidence of Indonesian EFL university students. Grounded in Bandura's (1997) self-efficacy theory and Byram's (2020) Intercultural Communicative Competence (ICC) framework, the study employed purposive sampling to recruit a bounded sample of three (n=3) Indonesian undergraduate participants, all of whom had completed at least one full AYIMUN delegation cycle. Data were generated through semi-structured interviews, reflective journals, and where available, observational records, and were analyzed using thematic analysis framework by Braun and Clarke (2006). The findings reveal that AYIMUN participation meaningfully strengthens students' public speaking confidence across four key dimensions: enhanced self-assurance, improved speech clarity and organizational coherence, greater spontaneity in impromptu communication, and heightened intercultural communicative awareness. Participants also reported concurrent growth in complementary competencies including critical thinking, negotiation, and leadership which functioned as catalysts for broader communicative development. These contributions must, however, be interpreted within the study's epistemological and methodological boundaries: the small purposive sample necessarily constrains the transferability of findings; the predominant reliance on self-reported data introduces potential recall and social desirability biases; and the single-site, single-event design delimits generalizability across diverse MUN contexts. The study concludes that AYIMUN constitutes a high-impact experiential learning environment that simultaneously fosters public speaking confidence and intercultural competence among Indonesian EFL learners, carrying substantive implications for curriculum design, extracurricular policy, and future empirical inquiry in Indonesian higher education.